The Effect of Pioglitazone and Metformin on Liver Function Tests, Insulin Resistance, and Liver Fat Content in Nonalcoholic Fatty Liver Disease: A Randomized Double Blinded Clinical Trial - Razavizade, Mohsen (Kowsar, 2013)
BACKGROUND: Non-alcoholic fatty liver disease (NAFLD) is considered as the hepatic manifestation of insulin resistance (IR) syndrome. The effect of insulin sensitizers on liver function tests and metabolic indices in NAFLD patients is a matter of debate. OBJECTIVES: The aim of study was to compare the effects of two different insulin sensitizers, pioglitazone, and metformin, on liver function tests (LFT), lipid profile, homeostasis model assessment-IR (HOMA-IR) index, and liver fat content (LFC) in NAFLD patients. MATERIALS AND METHODS: This double blind clinical trial was performed on patients who were referred to a gastroenterology clinic with evidence of fatty liver in ultrasonography. After excluding other causes, participants with persistent elevated alanine aminotransferase (ALT) levels and “NAFLD liver fat score” greater than -0.64 were presumed to have NAFLD and were enrolled. They were randomly assigned to take metformin (1 g/day) or pioglitazone (30 mg/day) for four months. Fasting serum glucose (FSG), ALT, aspartate aminotransferase (AST), alkaline phosphatase (ALP), triglyceride, cholesterol (CHOL), high and low density lipoprotein (HDL, LDL), HOMA-IR, and LFC were checked at the baseline, two and four months post-treatment. LFC was measured by a validated formula. RESULTS: Eighty patients (68 males) with mean age of 35.27 (± 7.98) were included. After 2 months, LFT was improved significantly in the pioglitazone group and did not change in the metformin group. After four months, both medications significantly decreased serum levels of LFT, FSG, CHOL, LDL, HOMA-IR, and LFC, and increased serum level of HDL. No statistically significant differences were seen between the two treatment groups with regard to the changes of laboratory parameters and LFC from baseline to four months post-treatment. CONCLUSIONS: During the four months, the use of metformin (1 g/day) and pioglitazone (30 mg/day) were safe and might have equally affected LFT, HOMA-IR, lipid profile, and LFC in NAFLD patients.